2017
DOI: 10.1111/cdev.12815
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of First‐Hand Testimony and Hearsay on Children's Belief in the Improbable

Abstract: Children (3.5-8.5 years; n = 105) heard claims about the occurrence of improbable or impossible events, then were asked whether the events could really happen. Some claims were based on informants' first-hand observations and others were hearsay. A baseline group (n = 56) reported their beliefs about these events without hearing testimony. Neither first-hand claims nor hearsay influenced beliefs about impossible events, which remained low across the age range. Hearsay (but not first-hand claims) did influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 43 publications
4
35
0
Order By: Relevance
“…In this experiment and the next one, we aimed to test 20 children per age-in-years per between-subjects condition, and randomly assigned equal numbers of children at age-each-inyears to each condition. We determined this sample size as it has sufficed to reveal significant effects in past work in this area of research (e.g., Bowman-Smith et al, 2018;Lane et al, 2018).…”
Section: Experiments 1 Methodsmentioning
confidence: 99%
“…In this experiment and the next one, we aimed to test 20 children per age-in-years per between-subjects condition, and randomly assigned equal numbers of children at age-each-inyears to each condition. We determined this sample size as it has sufficed to reveal significant effects in past work in this area of research (e.g., Bowman-Smith et al, 2018;Lane et al, 2018).…”
Section: Experiments 1 Methodsmentioning
confidence: 99%
“…But it is not until adulthood that people largely accept that improbable events can happen (Shtulman & Carey, 2007). This pattern of findings has proven robust (Cook & Sobel, 2011;Lane, Ronfard, & El-Sherif, 2018;Lane, Ronfard, Francioli, & Harris, 2016;Nancekivell & Friedman, 2017;Nolan-Reyes, Callanan, & Haigh, 2016;Shtulman, 2009;Shtulman & Phillips, 2018;Weisberg & Sobel, 2012).…”
mentioning
confidence: 99%
“…Children ages 4 years and older express stronger belief in entities with purported capacities that accord with their intuitions than capacities that contradict those intuitions . Although claims can strongly and swiftly influence preschoolers' beliefs in the occurrence of nonnormative events, similar claims have much less influence on their beliefs about events that defy their naïve theories . And preschoolers revise their beliefs more often after hearing claims about objects' properties that contradict their observations of inconsistent, probabilistic relations than after hearing claims that contradict their observations of consistent, deterministic relations .…”
Section: Factors That Influence Belief In Counterperceptual and Countmentioning
confidence: 98%
“…Whether claims influence children's beliefs about the possibility of purported events depends on the type of claim and the type of event. In one study, when speakers reported seeing nonnormative but plausible events occur firsthand (e.g., “I saw someone …”), preschoolers reported that these events could not occur . However, when speakers provided secondhand claims (e.g., “Someone told me they …”), preschoolers judged more often that the events could occur.…”
Section: Developmental Trends: Belief In Counterperceptual and Countementioning
confidence: 99%
See 1 more Smart Citation